A Content Analysis of Online Brand Personality of 4 Universities in Ghana - Amartey, Rhodalene; Austin, Nathan (Journal of Education and Practice, 2019)
The purpose of the study is to understand brand personality of four (4) universities in Ghana as communicated via their websites. Data was extracted from the websites of the 4 universities unto a word document. The text was analyzed using a content analysis technique. The Nvivo software version 12 was used to code the data. The results showed that the four (4) universities exhibit certain brand personality traits on their websites. For example, Kwame Nkrumah University of Science and Technology School of Business (KNUST Business School) and the University of Ghana Business School (UGBS) portrayed the following brand personality traits; competence, excitement, ruggedness, sincerity and sophistication. The University of Cape Coast School of Business (UCC School of Business) and the University of Education Winneba Faculty of Business (UEW Faculty of Business) exhibited the following brand personality traits; competence, ruggedness, sincerity and sophistication. The study concludes that the universities understand brand personality and strategically communicate them on their websites.
Research Article
Keywords: Brand Personality; Branding; Universities in Ghana; Content aAnalysis